Degradation of Rhodamine B by manganese residue activated peroxymonosulfate - ZHENG Guoqing; HUANG Yukun; HAN Yaocong; XUE Xingyong; LU Yanyue; LAN Lihong; CHEN Zhennan (Gongye shui chuli)
Manganese residue was used to activate peroxymonosulfate(PMS) for Rhodamine B(RhB) degradation. The physichemical properties of manganese residue were analyzed by X-ray diffractometer, specific surface area and porosity analyzer and Fourier transform infrared spectrometer. The effects of manganese residue dosage, PMS concentration, temperature, pH, and RhB concentration of the solution on RhB degradation were studied. The reusability of manganese residue and mechanism of RhB degradation using PMS activated by manganese residue were also investigated. The results showed that manganese residue used in this study contained abundant Fe3O4, with a saturation magnetization of 8.67 emu/g and a specific surface area of 29.95 m2/g. The pores in manganese residue were predominantly mesoporous. The removal rate of RhB could reach 97.6% at 120 min under the conditions of temperature of 25 ℃, RhB concentration of 20 mg/L, manganese residue dosage of 2.0 g/L, PMS concentration of 0.50 mmol/L, pH of 4.9, and still could maintain 84.2% after 5 cycles. In the degradation process, 1O2, O2·- and ·OH were all involved in the reaction, with 1O2 playing a dominant role.